Experimental and numerical analysis of buoyancy-induced flow in inclined triangular enclosures - Öztop, Hakan Fehmi; Varol, Yasin; Koca, Ahmet; Firat, Mujdat (Pergamon-Elsevier Science Ltd, 2012)
The buoyancy-induced heat transfer and fluid flow in a triangular enclosure are investigated both numerically and experimentally. The enclosure is heated from one wall and the adjacent wall is insulated. Hypotenuse of the triangle is cooled isothermally. The numerical tests and experiments covered a range of Rayleigh number, Ra, from 1.5 x 10(4) to 1.5 x 10(5). The local and average Nusselt numbers are given for different orientation angles. A code was written based on finite difference method in Fortran platform to solve governing equations of natural convection. Experimental and numerical results show good agreement. It is observed that inclination angle can be used as a control parameter for heat transfer. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Triangular enclosure; Experimental; Numerical analysis; Natural convection